Heterogeneously Nd3+ doped single nanoparticles for NIR-induced heat conversion, luminescence, and thermometry. Issue 24 (6th June 2017) - Marciniak, Lukasz; Pilch, Aleksandra; Arabasz, Sebastian; Jin, Dayong; Bednarkiewicz, Artur
Abstract : The current frontier in nanomaterials engineering is to intentionally design and fabricate heterogeneous nanoparticles with desirable morphology and composition, and to integrate multiple functionalities through highly controlled epitaxial growth. Abstract : The current frontier in nanomaterials engineering is to intentionally design and fabricate heterogeneous nanoparticles with desirable morphology and composition, and to integrate multiple functionalities through highly controlled epitaxial growth. Here we show that heterogeneous doping of Nd 3+ ions following a core–shell design already allows three optical functions, namely efficient ( η > 72%) light-to-heat conversion, bright NIR emission, and sensitive ( S R > 0.1% K −1 ) localized temperature quantification, to be built within a single ca. 25 nm nanoparticle. Importantly, all these optical functions operate within the transparent biological window of the NIR spectral region ( λ exc ∼ 800 nm, λ emi ∼ 860 nm), in which light scattering and absorption by tissues and water are minimal. We find NaNdF4 as a core is efficient in absorbing and converting 808 nm light to heat, while NaYF4 :1%Nd 3+ as a shell is a temperature sensor based on the ratio-metric luminescence reading but an intermediate inert spacer shell, e.g. NaYF4, is necessary to insulate the heat convertor and thermometer by preventing the possible Nd–Nd energy relaxation. Moreover, we notice that while temperature sensitivity and luminescence intensity are optically stable, increased excitation intensity to generate heat above room temperature may saturate the sensing capacity of temperature feedback. We therefore propose a dual beam photoexcitation scheme as a solution for possible light-induced hyperthermia treatment.